Mobile genetic elements in shaping Klebsiella pneumoniae pathogenicity - Li, Yanbing; Farzana, Refath (Frontiers in Microbiology, 2026)
Klebsiella pneumoniae has evolved from an opportunistic pathogen into a formidable global threat, with hypervirulent strains now causing severe infections in healthy individuals and carbapenem-resistant variants achieving mortality rates exceeding 42%. This transformation can be driven by mobile genetic elements including plasmids, integrative conjugative elements (ICE), insertion sequences (ISs), transposons, and integrons. Recent discoveries reveal that these elements employ sophisticated mechanisms: conjugative virulence plasmids dissemination across bacterial populations; ICEs-mediated virulence traits transfer; and hybrid genetic elements simultaneously confer virulence and antimicrobial resistance. Understanding these molecular mechanisms is critical for developing targeted diagnostics and therapeutics that disrupt mobile element mobility, offering promising strategies to combat the convergence of hypervirulence and resistance in this WHO priority pathogen.